Evaluation of test characteristics for outcome measures used in Raynaud's phenomenon clinical trials - Gladue, Heather (2013)
OBJECTIVE: Randomized controlled trials (RCTs) in Raynaud's phenomenon (RP) have shown conflicting efficacy data. Also, there is no consensus on the outcome measures that should be used. Our objectives were: 1) assess the reliability of individual core set measures used in 3 RCTs; 2) evaluate the placebo response for individual core set measures; and 3) determine if a composite of individual core set measures will decrease the placebo response which may improve our ability to see treatment effects in future trials. PATIENTS AND METHODS: We analyzed core set measures from 249 patients in the placebo-treated groups from 3 RCTs. Core set measures analyzed included Raynaud's condition score (RCS), patient and physician assessment of RP, pain, numbness, and tingling during an RP attack, average number of attacks/day, and duration of attacks. ICC correlation coefficients were calculated during the run-in period to the RCTs. RESULTS: ICC coefficients of ≥0.70 were observed for RCS, attack symptoms, and average attacks/day. A high placebo response rate was observed for all individual core measures except the duration of attacks. For the RCS, the placebo response ranged from 56% with >10% improvement to 20% with ≥60% improvement. In contrast, placebo response rates of 10–20% were observed when several core set measures were combined to develop a composite score. CONCLUSIONS: Outcome measures used in RP RCTs are associated with marked variability. Combination of outcome measures is associated with low placebo responses. Future studies are needed to assess if a composite score will be able to differentiate placebo from an effective agent.